Sunday

April 20, 2014

April 20, 2014

Posted by **Jamie** on Sunday, September 27, 2009 at 12:53am.

(-8B^2)=

-8B^2=

SOLVE USING THE ADDITION PRINCIPLE.

3.8=S=0.1. THE SOLUTION IS S=

THANK YOU

**Related Questions**

Algebra 1A - evaluate (-8b)^2 and -8b^2 when b=10. (-8b^2)= -8b^2=

Algebra 1 - Give the reason (property) for each step in the simplification. 8(a...

Math - How would I do: sqrt32a^8b + sqrt50a^16b Are the exponents 8b and 16b or ...

Math - Can someone please help me with an algebra problem? -|4-8b|=12 I really ...

ALGEBRA - Use the definition of logarithm to simplify each expression. (a) )log_...

Algebra - Multiply 5a^3+4a^2 8b^6-6ab^6 _________ * __________ 6ab-8b 5a^2+4a

algebra - Identify the property or rule that justifies each step in the ...

algebra 1 - 7a+[4a-6b-(8a+2b)] ok so you would get this 7a+[4a-6b-8a-2b]<--- ...

geometry - Solve y= 5/8b+10 for b

math - (4,-2) and (2,-8) lie on the line Ax-2By = 28. What is the value of A? ...